Cedar Cove : 92 Pacific Boulevard - Book 9 - Macomber, Debbie; Burr, Sandra (Grand Haven, MI : Brilliance Audio, 2009)
After his romance with ex-flame Faith Beckworth is all but extinguished, local sheriff Troy Davis contends with remains found in a cave, his friend Judge Olivia Griffin's battle with cancer, and a series of break-ins at Faith's home.
Unabridged.
Compact discs.
Read by Sandra Burr.
Keywords: Cedar Cove (Wash. : Imaginary place) -- Fiction; City and town life -- Fiction -- Washington (State); Audiobooks